2021
DOI: 10.1186/s12889-021-10178-0
|View full text |Cite
|
Sign up to set email alerts
|

Uganda’s increasing dependence on development partner’s support for immunization – a five year resource tracking study (2012 – 2016)

Abstract: Background In Uganda, there are persistent weaknesses in obtaining accurate, reliable and complete data on local and external investments in immunization to guide planning, financing, and resource mobilization. This study aimed to measure and describe the financial envelope for immunization from 2012 to 2016 and analyze expenditures at sub-national level. Methods The Systems of Health Accounts (SHA) 2011 methodology was used to quantify and map the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Uganda’s health system comprises of both the private and public sector in terms of infrastructure, ownership and delivery of health services [ 39 , 40 ]. The health system is decentralized and hierarchical with seven levels starting from the household/village level and culminating at national referral institutions and the Ministry of Health [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uganda’s health system comprises of both the private and public sector in terms of infrastructure, ownership and delivery of health services [ 39 , 40 ]. The health system is decentralized and hierarchical with seven levels starting from the household/village level and culminating at national referral institutions and the Ministry of Health [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, the latest figures report private expenditure as a percentage of Current Health Expenditure (CHE) to be 41% and out-of-pocket expenditure at 38% [ 43 ]. Health financing remains a key national challenge and the recommended Abuja target 15% of the GDP apportioned to health [ 40 , 44 , 45 ] has never been achieved, with average health sector allocations ranging from 6 to 9% [ 45 , 46 ]. In particular, the low funding for Uganda’s healthcare system continues to create an ongoing challenge of insufficient health workforce numbers [ 47 ] which has sometimes been mitigated by task shifting since 1918 [ 48 ] and which the evidence shows to have improved quality of care in the treatment of HIV/AIDS, tuberculosis, maternal, newborn and child health (MNCH) programs as well as malaria [ 49 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, OOP payment is associated with inequity in access, catastrophic expenditure and impoverishment 22 , 25 , 28 , 39 , 50 , 52 . Secondly, development partners' funding has issues of unpredictability and fragmentation 27 , 51 , 53 – 55 .…”
Section: Resultsmentioning
confidence: 99%
“…Participants reported negotiating credit with local private transport companies including commercial motorcycle drivers, while awaiting the release of PHC funds for use as a refund. According to Ministry of Health EPI guidelines, the transportation of vaccines from the district vaccine store to lower health facilities is the mandate of the district health office which can be achieved if transport means and fuel is availed through PHC funds [ 22 ]. Our study revealed that this transportation of vaccines was affected due to lack of available transport facilities.…”
Section: Discussionmentioning
confidence: 99%